Exploring the Experiences of Co-morbid Pain and Depression in Older African American Women and Their Preferred Management Strategies - Drazich, Brittany F.; Jenkins, Emerald; Nkimbeng, Manka; Abshire Saylor, Martha; Szanton, Sarah L.; Wright, Rebecca; Beach, Mary Catherine; Taylor, Janiece L. (Frontiers in Pain Research, 2022)
The intersection of race, gender, and age places older African American women at an increased risk for untreated physical pain and depression that can significantly diminish their quality of life. The objectives of this study were to 1) explore older African American women’s perceptions of pain and depressive symptoms and how these symptoms influence each other, and 2) explore effective pain and depression alleviation strategies used by the women. We conducted five focus groups with older African American women (N=18). We used deductive coding to analyze focus group transcripts and qualitative description to summarize themes. We identified five major themes: 1) Spiritual Suffering from Linked Pain and Depression 2) Lack of Understanding from Healthcare Providers 3) Push Through and Live Through 4) Medications Not Worth the Risk and 5) Strategies for Pain and Depression. This study offers insight into the experiences of pain and depression in older African American women, and alleviation strategies they perceive as effective. These qualitative findings may be used to inform interventions for older African American women who experience pain and depressive symptoms.